Rambutan-shaped ZnO-N, S dual-doped porous carbon composite electrode material and preparation method
By preparing rambutan-like ZnO-N,S double-doped porous carbon composite electrode material, the problems of poor conductivity and cycle stability of the negative electrode material of lithium-ion battery are solved, and high conductivity and good cycle stability are achieved.
Patent Information
- Application Number
- CN202211211049.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-30
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-09-30
AI Technical Summary
The conventional lithium-ion battery negative electrode material ZnO has poor conductivity and poor cycle stability.
The preparation method of rambutan-like ZnO-N,S double-doped porous carbon composite electrode material is adopted to catalyze the reaction of thiophene and succinyl chloride to form 2,5-dithienylpyrrole derivatives, and after polymerization, it is crosslinked with terephthaldehyde, and calcined to form N,S co-doped porous carbon, and then combined with zinc oxide to form rambutan-like ZnO-N,S double-doped porous carbon.
The conductivity and cyclic stability of the negative electrode material of lithium-ion battery is improved, the volume expansion during charging and discharging is avoided, and the transmission capacity of electrons and ions is enhanced.
Smart Images

Figure CN115425216B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery negative electrodes, in particular to a rambutan-shaped ZnO-N, S dual-doped porous carbon composite electrode material and a preparation method thereof. Background Art
[0002] Lithium-ion battery is a new energy source with great potential. It has received more and more attention in today's society. It is an energy storage material with research significance and practical value. Compared with other secondary power sources, lithium-ion battery has many advantages, such as small size, light weight, high specific capacity, good cycle stability, low self-discharge, and electrode materials do not contain harmful heavy metal elements. It has the advantage of being green and environmentally friendly, which is in line with the development trend of today's society.
[0003] Lithium-ion batteries are composed of positive electrode materials, negative electrode materials, electrolytes, separators and current collectors. Among them, positive electrode materials and negative electrode materials are the main components of lithium-ion batteries, especially negative electrode materials, which largely determine the properties of lithium-ion batteries. At present, most commercial lithium-ion battery negative electrode materials are carbon materials, which have the characteristics of low price and environmental friendliness. The sources of porous carbon materials are very wide. In addition to traditional biomass raw materials, polymer materials can also be used as carbon sources for porous carbon, such as polypyrrole, polythiophene and other conductive polymers, but the specific capacity of a single carbon material is low. Metal oxides such as nano zinc oxide, nano tin dioxide, nano nickel oxide, etc. have high theoretical specific capacity and excellent lithium storage performance. They are suitable negative electrode materials for lithium-ion batteries. After being composited with carbon materials, they not only solve the problem of low specific capacity of single carbon materials, but also avoid the volume expansion of metal oxides during charging and discharging. At the same time, by incorporating heteroatoms such as nitrogen atoms, boron atoms, sulfur atoms, etc., the performance of negative electrode materials can be greatly improved, thereby optimizing the performance of lithium-ion batteries.
[0004] 1. Technical issues to be resolved
[0005] In view of the shortcomings of the prior art, the present invention provides a rambutan-shaped ZnO-N, S dual-doped porous carbon composite electrode material and a preparation method, which solves the problem that ZnO has poor conductivity and poor cycle stability as an electrode material for lithium-ion batteries.
[0006] (II) Technical solution
[0007] To achieve the above object, the present invention provides the following technical solution: a rambutan-shaped ZnO-N, S dual-doped porous carbon composite electrode material, the rambutan-shaped ZnO-N, S dual-doped porous carbon composite electrode material and the preparation method are as follows:
[0008] (1) Using aluminum chloride as a catalyst, thiophene and succinyl chloride react to obtain 1,4-bis(2-thienyl)-1,4-butanedione, which then reacts with p-phenylenediamine to obtain a 2,5-dithienylpyrrole derivative containing an aromatic amino group, with the molecular formula C 18 H 14 N 2 S 2 ;
[0009] (2) Using 2,5-dithienylpyrrole derivatives as reactants, a polymerization reaction occurs under the action of n-butyl lithium and copper chloride as initiators to obtain polydithienylpyrrole;
[0010] (3) adding polydithienyl pyrrole to a 20%-35% acetic acid solution, stirring and mixing evenly, adding terephthalaldehyde, stirring and mixing evenly, causing a cross-linking reaction, filtering, washing, and drying after the reaction is completed to obtain a super-cross-linked polydithienyl pyrrole;
[0011] (4) adding the hyper-crosslinked polydithienyl pyrrole into a tube furnace and calcining it in a nitrogen atmosphere. After the calcination, cooling is performed, and the obtained sample is soaked in deionized water for 2-4 hours and then dried to obtain a N, S co-doped carbon precursor.
[0012] (5) uniformly mixing the N, S co-doped carbon precursor and potassium hydroxide, transferring them to a tube furnace, and calcining them in an argon atmosphere. After the calcination, immersing, washing to neutrality, and drying, thereby obtaining N, S co-doped porous carbon;
[0013] (6) Add sorbitol and zinc nitrate to deionized water and ethanol, stir well, then add sodium hydroxide and N, S co-doped porous carbon, mix well, transfer the mixed solution to a reactor, and perform an aging reaction. After the reaction is completed, centrifuge, wash, and dry to obtain a rambutan-like ZnO-N, S co-doped porous carbon composite electrode material.
[0014] Preferably, in step (3), the mass ratio of polydithienylpyrrole to terephthalaldehyde is 100:15-25.
[0015] Preferably, the temperature of the cross-linking reaction in step (3) is 50-65° C., and the time of the cross-linking reaction is 6-12 h.
[0016] Preferably, in step (4), the heating rate of calcination is 2-5°C / min, the calcination temperature is 750-850°C, and the calcination time is 1-2h.
[0017] Preferably, in step (5), the mass ratio of the N, S co-doped carbon precursor to potassium hydroxide is 100:350-450.
[0018] Preferably, in step (5), the heating rate of calcination is 2-5°C / min, the calcination temperature is 800-850°C, and the calcination time is 2-3h.
[0019] Preferably, in step (6), the mass ratio of sorbitol, zinc nitrate, sodium hydroxide and N, S co-doped porous carbon is 40-60:52-76:110-160:100.
[0020] Preferably, the aging reaction temperature in step (6) is 80-100° C., and the aging reaction time is 5-10 h.
[0021] 3. Beneficial technical effects
[0022] Compared with the prior art, the present invention has the following beneficial technical effects:
[0023] The rambutan-shaped ZnO-N, S dual-doped porous carbon composite electrode material uses a 2,5-dithienyl pyrrole derivative as a polymerization monomer, and a polymerization reaction occurs under the action of n-butyl lithium and copper chloride as initiators to obtain polydithienyl pyrrole containing aromatic amino groups. The aromatic amino groups on the polydithienyl pyrrole and the aldehyde groups on terephthalaldehyde undergo a Schiff base crosslinking reaction to obtain a super-crosslinked polydithienyl pyrrole, which is calcined in a nitrogen atmosphere, using the super-crosslinked polydithienyl pyrrole as a carbon source, thiophene rings as a sulfur source, and pyrrole rings as a nitrogen source to obtain a N, S co-doped carbon precursor, and then potassium hydroxide is used as a catalyst. Porogen is calcined to obtain N, S co-doped porous carbon, and then zinc nitrate is used as zinc source and added to N, S co-doped porous carbon. Under the action of sorbitol, the growth rate of the low-index surface of zinc oxide polymerization is affected, and zinc hydroxide nanoparticles are first formed. As the reaction time increases, agglomeration occurs and they grow along powerful crystal planes. As the temperature of the reaction system increases, zinc hydroxide generates zinc oxide nucleation elements. During the process of dissolution and recrystallization, the needle-shaped nano zinc oxide is orderly aggregated and combined into a rambutan shape, which grows evenly on the porous carbon matrix to obtain rambutan-shaped ZnO-N, S co-doped porous carbon.
[0024] The invention discloses a rambutan-shaped ZnO-N, S dual-doped porous carbon composite electrode material. The porous carbon is a carbon material with a large specific surface area and rich pore structure. The synthesized rambutan-shaped zinc oxide also has an ultra-large specific surface area and pore structure. The material is grown on the porous carbon matrix. The two have strong structural stability and electron diffusion rate. Zinc oxide, as a transition metal oxide, has excellent specific capacity and energy density, but the attenuation of the specific capacity is obvious during the charge and discharge process, and the electrical conductivity is poor. By compounding with carbon materials, the porous carbon material has excellent electrical conductivity and chemical stability, can effectively avoid structural collapse caused by volume expansion and improve the electrical conductivity of the electrode material. The incorporation of nitrogen atoms in the porous carbon improves the wettability between the porous carbon and the electrolyte, and provides a path for the transmission of electrons and ions. The incorporation of sulfur atoms produces more active sites on the porous carbon material, which is convenient for charge transfer, improves the performance of the negative electrode material of the lithium ion battery, and makes the lithium ion battery have excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a diagram of the synthesis mechanism of hyper-crosslinked polydithienylpyrrole. DETAILED DESCRIPTION
[0026] To achieve the above objectives, the present invention provides the following specific implementation methods and examples: A method for preparing a rambutan-shaped ZnO-N, S dual-doped porous carbon composite electrode material is as follows:
[0027] (1) Using aluminum chloride as a catalyst, thiophene and succinyl chloride react to obtain 1,4-bis(2-thienyl)-1,4-butanedione, which then reacts with p-phenylenediamine to obtain a 2,5-dithienylpyrrole derivative containing an aromatic amino group, with the molecular formula C 18 H 14 N 2 S 2 ;
[0028] (2) Using 2,5-dithienylpyrrole derivatives as reactants, a polymerization reaction occurs under the action of n-butyl lithium and copper chloride as initiators to obtain polydithienylpyrrole;
[0029] (3) Add 20%-35% acetic acid solution as a solvent to a three-necked flask, then add polydithienyl pyrrole, stir and mix evenly, then add terephthalaldehyde, the mass ratio of the added polydithienyl pyrrole to terephthalaldehyde is 100:15-25, stir and mix evenly, cross-linking reaction occurs at 50-65° C., the cross-linking reaction time is 6-12 hours, after the reaction is completed, filter, wash with deionized water, and dry to obtain super-cross-linked polydithienyl pyrrole;
[0030] (4) adding hyper-crosslinked polydithienylpyrrole into a crucible, placing it in a tube furnace, and calcining it in a nitrogen atmosphere at a heating rate of 2-5°C / min, a calcination temperature of 750-850°C, and a calcination time of 1-2h. After the calcination, cooling is performed, and the obtained sample is soaked in deionized water for 2-4h and then dried to obtain a N,S co-doped carbon precursor;
[0031] (5) Adding N, S co-doped carbon precursor and potassium hydroxide in a mass ratio of 100:350-450 into a mortar, mixing evenly, transferring to a tube furnace, calcining in an argon atmosphere, the calcination heating rate is 2-5 ° C / min, the calcination temperature is 800-850 ° C, the calcination time is 2-3h, after the calcination is completed, impregnating with dilute hydrochloric acid, and then washing with a large amount of deionized water until neutral, and drying to obtain N, S co-doped porous carbon;
[0032] (6) Add deionized water and ethanol to a beaker, then add sorbitol and zinc nitrate, stir well, then add sodium hydroxide and N, S co-doped porous carbon, the mass ratio of sorbitol, zinc nitrate, sodium hydroxide and N, S co-doped porous carbon is 40-60:52-76:110-160:100, mix well, transfer the mixed solution to a reactor, and age at 80-100°C for 5-10 hours. After the reaction is completed, centrifuge, wash with deionized water and ethanol, and dry to obtain a rambutan-like ZnO-N, S dual-doped porous carbon composite electrode material.
[0033] Example 1
[0034] (1) Using aluminum chloride as a catalyst, thiophene and succinyl chloride react to obtain 1,4-bis(2-thienyl)-1,4-butanedione, which then reacts with p-phenylenediamine to obtain a 2,5-dithienylpyrrole derivative containing an aromatic amino group, with the molecular formula C 18 H 14 N 2 S 2 ;
[0035] (2) Using 2,5-dithienylpyrrole derivatives as reactants, a polymerization reaction occurs under the action of n-butyl lithium and copper chloride as initiators to obtain polydithienylpyrrole;
[0036] (3) Add 20% acetic acid solution as a solvent to a three-necked flask, then add polydithienyl pyrrole, stir and mix evenly, then add terephthalaldehyde, the mass ratio of the added polydithienyl pyrrole to terephthalaldehyde is 100:15, stir and mix evenly, cross-linking reaction occurs at 50° C., the cross-linking reaction time is 6 hours, after the reaction is completed, filter, wash with deionized water, and dry to obtain super-cross-linked polydithienyl pyrrole;
[0037] (4) adding hyper-crosslinked polydithienylpyrrole into a crucible, placing it in a tube furnace, and calcining it in a nitrogen atmosphere at a heating rate of 2°C / min, a calcination temperature of 750°C, and a calcination time of 1 h. After the calcination, cooling is performed, and the obtained sample is soaked in deionized water for 2 h, and then dried to obtain a N, S co-doped carbon precursor;
[0038] (5) Adding N, S co-doped carbon precursor and potassium hydroxide in a mass ratio of 100:350 into a mortar, mixing evenly, transferring to a tube furnace, calcining in an argon atmosphere, the calcination heating rate is 2 ° C / min, the calcination temperature is 800 ° C, the calcination time is 2h, after the calcination is completed, impregnating with dilute hydrochloric acid, and then washing with a large amount of deionized water until neutral, and drying to obtain N, S co-doped porous carbon;
[0039] (6) Deionized water and ethanol were added to a beaker, followed by sorbitol and zinc nitrate. After stirring, sodium hydroxide and N, S co-doped porous carbon were added. The mass ratio of sorbitol, zinc nitrate, sodium hydroxide and N, S co-doped porous carbon was 40:52:110:100. After mixing, the mixed solution was transferred to a reactor and aged at 80 °C for 5 h. After the reaction, the mixture was centrifuged, washed with deionized water and ethanol, and dried to obtain a rambutan-like ZnO-N, S co-doped porous carbon composite electrode material.
[0040] Example 2
[0041] (1) Using aluminum chloride as a catalyst, thiophene and succinyl chloride react to obtain 1,4-bis(2-thienyl)-1,4-butanedione, which then reacts with p-phenylenediamine to obtain a 2,5-dithienylpyrrole derivative containing an aromatic amino group, with the molecular formula C 18 H 14 N 2 S 2 ;
[0042] (2) Using 2,5-dithienylpyrrole derivatives as reactants, a polymerization reaction occurs under the action of n-butyl lithium and copper chloride as initiators to obtain polydithienylpyrrole;
[0043] (3) Add 25% acetic acid solution as a solvent to a three-necked flask, then add polydithienyl pyrrole, stir and mix evenly, then add terephthalaldehyde, the mass ratio of the added polydithienyl pyrrole to terephthalaldehyde is 100:18, stir and mix evenly, cross-linking reaction occurs at 55°C, the cross-linking reaction time is 8 hours, after the reaction is completed, filter, wash with deionized water, and dry to obtain super-cross-linked polydithienyl pyrrole;
[0044] (4) adding hyper-crosslinked polydithienylpyrrole into a crucible, placing it in a tube furnace, and calcining it in a nitrogen atmosphere at a heating rate of 3°C / min, a calcination temperature of 780°C, and a calcination time of 1.2 h. After the calcination, cooling is performed, and the obtained sample is soaked in deionized water for 2.5 h, and then dried to obtain a N, S co-doped carbon precursor;
[0045] (5) Adding N, S co-doped carbon precursor and potassium hydroxide in a mass ratio of 100:380 into a mortar, mixing evenly, transferring to a tube furnace, calcining in an argon atmosphere, the calcination heating rate is 3 ° C / min, the calcination temperature is 820 ° C, the calcination time is 2.2 h, after the calcination is completed, impregnating with dilute hydrochloric acid, and then washing with a large amount of deionized water until neutral, and drying to obtain N, S co-doped porous carbon;
[0046] (6) Deionized water and ethanol were added to a beaker, followed by sorbitol and zinc nitrate. After stirring, sodium hydroxide and N, S co-doped porous carbon were added. The mass ratio of sorbitol, zinc nitrate, sodium hydroxide and N, S co-doped porous carbon was 45:58:125:100. After mixing, the mixed solution was transferred to a reactor and aged at 85 °C for 6 h. After the reaction, the mixture was centrifuged, washed with deionized water and ethanol, and dried to obtain a rambutan-like ZnO-N, S co-doped porous carbon composite electrode material.
[0047] Example 3
[0048] (1) Using aluminum chloride as a catalyst, thiophene and succinyl chloride react to obtain 1,4-bis(2-thienyl)-1,4-butanedione, which then reacts with p-phenylenediamine to obtain a 2,5-dithienylpyrrole derivative containing an aromatic amino group, with the molecular formula C 18 H 14 N 2 S 2 ;
[0049] (2) Using 2,5-dithienylpyrrole derivatives as reactants, a polymerization reaction occurs under the action of n-butyl lithium and copper chloride as initiators to obtain polydithienylpyrrole;
[0050] (3) Add 30% acetic acid solution as a solvent to a three-necked flask, then add polydithienyl pyrrole, stir and mix evenly, then add terephthalaldehyde, the mass ratio of the added polydithienyl pyrrole to terephthalaldehyde is 100:20, stir and mix evenly, cross-linking reaction occurs at 55° C., the cross-linking reaction time is 10 hours, after the reaction is completed, filter, wash with deionized water, and dry to obtain super-cross-linked polydithienyl pyrrole;
[0051] (4) adding hyper-crosslinked polydithienylpyrrole into a crucible, placing it in a tube furnace, and calcining it in a nitrogen atmosphere at a heating rate of 4°C / min, a calcination temperature of 820°C, and a calcination time of 1.5 h. After the calcination, cooling is performed, and the obtained sample is soaked in deionized water for 3 h, and then dried to obtain a N, S co-doped carbon precursor;
[0052] (5) Adding N, S co-doped carbon precursor and potassium hydroxide in a mass ratio of 100:410 into a mortar, mixing evenly, transferring to a tube furnace, calcining in an argon atmosphere, the calcination heating rate is 4 ° C / min, the calcination temperature is 840 ° C, the calcination time is 2.5 h, after the calcination is completed, impregnating with dilute hydrochloric acid, and then washing with a large amount of deionized water until neutral, and drying to obtain N, S co-doped porous carbon;
[0053] (6) Deionized water and ethanol were added to a beaker, followed by sorbitol and zinc nitrate. After stirring, sodium hydroxide and N, S co-doped porous carbon were added. The mass ratio of sorbitol, zinc nitrate, sodium hydroxide and N, S co-doped porous carbon was 52:65:135:100. After mixing, the mixed solution was transferred to a reactor and aged at 90 °C for 7 h. After the reaction, the mixture was centrifuged, washed with deionized water and ethanol, and dried to obtain a rambutan-like ZnO-N, S co-doped porous carbon composite electrode material.
[0054] Example 4
[0055] (1) Using aluminum chloride as a catalyst, thiophene and succinyl chloride react to obtain 1,4-bis(2-thienyl)-1,4-butanedione, which then reacts with p-phenylenediamine to obtain a 2,5-dithienylpyrrole derivative containing an aromatic amino group, with the molecular formula C 18 H 14 N 2 S 2 ;
[0056] (2) Using 2,5-dithienylpyrrole derivatives as reactants, a polymerization reaction occurs under the action of n-butyl lithium and copper chloride as initiators to obtain polydithienylpyrrole;
[0057] (3) Add 30% acetic acid solution as a solvent to a three-necked flask, then add polydithienyl pyrrole, stir and mix evenly, then add terephthalaldehyde, the mass ratio of the added polydithienyl pyrrole to terephthalaldehyde is 100:24, stir and mix evenly, cross-linking reaction occurs at 60° C., the cross-linking reaction time is 10 hours, after the reaction is completed, filter, wash with deionized water, and dry to obtain super-cross-linked polydithienyl pyrrole;
[0058] (4) adding hyper-crosslinked polydithienylpyrrole into a crucible, placing it in a tube furnace, and calcining it in a nitrogen atmosphere at a heating rate of 4°C / min, a calcination temperature of 820°C, and a calcination time of 1.5 h. After the calcination, cooling is performed, and the obtained sample is soaked in deionized water for 3.5 h, and then dried to obtain a N, S co-doped carbon precursor;
[0059] (5) Adding N, S co-doped carbon precursor and potassium hydroxide in a mass ratio of 100:430 into a mortar, mixing evenly, transferring to a tube furnace, calcining in an argon atmosphere, the calcination heating rate is 4 ° C / min, the calcination temperature is 840 ° C, the calcination time is 2.5 h, after the calcination is completed, impregnating with dilute hydrochloric acid, and then washing with a large amount of deionized water until neutral, and drying to obtain N, S co-doped porous carbon;
[0060] (6) Deionized water and ethanol were added to a beaker, followed by sorbitol and zinc nitrate. After stirring, sodium hydroxide and N, S co-doped porous carbon were added. The mass ratio of sorbitol, zinc nitrate, sodium hydroxide and N, S co-doped porous carbon was 55:68:150:100. After mixing, the mixed solution was transferred to a reactor and aged at 95 °C for 9 h. After the reaction, the mixture was centrifuged, washed with deionized water and ethanol, and dried to obtain a rambutan-like ZnO-N, S co-doped porous carbon composite electrode material.
[0061] Example 5
[0062] (1) Using aluminum chloride as a catalyst, thiophene and succinyl chloride react to obtain 1,4-bis(2-thienyl)-1,4-butanedione, which then reacts with p-phenylenediamine to obtain a 2,5-dithienylpyrrole derivative containing an aromatic amino group, with the molecular formula C 18 H 14 N 2 S 2 ;
[0063] (2) Using 2,5-dithienylpyrrole derivatives as reactants, a polymerization reaction occurs under the action of n-butyl lithium and copper chloride as initiators to obtain polydithienylpyrrole;
[0064] (3) Add 35% acetic acid solution as a solvent to a three-necked flask, then add polydithienyl pyrrole, stir and mix evenly, then add terephthalaldehyde, the mass ratio of the added polydithienyl pyrrole to terephthalaldehyde is 100:25, stir and mix evenly, cross-linking reaction occurs at 65°C, the cross-linking reaction time is 12h, after the reaction is completed, filter, wash with deionized water, and dry to obtain super-cross-linked polydithienyl pyrrole;
[0065] (4) adding hyper-crosslinked polydithienylpyrrole into a crucible, placing it in a tube furnace, and calcining it in a nitrogen atmosphere at a heating rate of 5°C / min, a calcination temperature of 850°C, and a calcination time of 2h. After the calcination, cooling is performed, and the obtained sample is soaked in deionized water for 4h and then dried to obtain a N,S co-doped carbon precursor;
[0066] (5) Adding N, S co-doped carbon precursor and potassium hydroxide in a mass ratio of 100:450 into a mortar, mixing evenly, transferring to a tube furnace, calcining in an argon atmosphere, the calcination heating rate is 5 ° C / min, the calcination temperature is 850 ° C, the calcination time is 3 h, after the calcination is completed, impregnating with dilute hydrochloric acid, and then washing with a large amount of deionized water until neutral, and drying to obtain N, S co-doped porous carbon;
[0067] (6) Deionized water and ethanol were added to a beaker, followed by sorbitol and zinc nitrate. After stirring, sodium hydroxide and N, S co-doped porous carbon were added. The mass ratio of sorbitol, zinc nitrate, sodium hydroxide and N, S co-doped porous carbon was 60:76:160:100. After mixing, the mixed solution was transferred to a reactor and aged at 100 °C for 10 h. After the reaction, the mixture was centrifuged, washed with deionized water and ethanol, and dried to obtain a rambutan-like ZnO-N, S dual-doped porous carbon composite electrode material.
[0068] Comparative Example 1
[0069] (1) Using aluminum chloride as a catalyst, thiophene and succinyl chloride react to obtain 1,4-bis(2-thienyl)-1,4-butanedione, which then reacts with p-phenylenediamine to obtain a 2,5-dithienylpyrrole derivative containing an aromatic amino group, with the molecular formula C 18 H 14 N 2 S 2 ;
[0070] (2) Using 2,5-dithienylpyrrole derivatives as reactants, a polymerization reaction occurs under the action of n-butyl lithium and copper chloride as initiators to obtain polydithienylpyrrole;
[0071] (3) Add 30% acetic acid solution as a solvent to a three-necked flask, then add polydithienyl pyrrole, stir and mix evenly, then add terephthalaldehyde, the mass ratio of the added polydithienyl pyrrole to terephthalaldehyde is 100:10, stir and mix evenly, cross-linking reaction occurs at 60° C., the cross-linking reaction time is 10 hours, after the reaction is completed, filter, wash with deionized water, and dry to obtain super-cross-linked polydithienyl pyrrole;
[0072] (4) adding hyper-crosslinked polydithienylpyrrole into a crucible, placing it in a tube furnace, and calcining it in a nitrogen atmosphere at a heating rate of 4°C / min, a calcination temperature of 820°C, and a calcination time of 1.5 h. After the calcination, cooling is performed, and the obtained sample is soaked in deionized water for 3 h, and then dried to obtain a N, S co-doped carbon precursor;
[0073] (5) Adding N, S co-doped carbon precursor and potassium hydroxide in a mass ratio of 100:300 into a mortar, mixing evenly, transferring to a tube furnace, calcining in an argon atmosphere, the calcination heating rate is 4 ° C / min, the calcination temperature is 820 ° C, the calcination time is 2.5 h, after the calcination is completed, impregnating with dilute hydrochloric acid, and then washing with a large amount of deionized water until neutral, and drying to obtain N, S co-doped porous carbon;
[0074] (6) Deionized water and ethanol were added to a beaker, followed by sorbitol and zinc nitrate. After stirring, sodium hydroxide and N, S co-doped porous carbon were added. The mass ratio of sorbitol, zinc nitrate, sodium hydroxide and N, S co-doped porous carbon was 30:38:90:100. After mixing, the mixed solution was transferred to a reactor and aged at 90 °C for 8 h. After the reaction, the mixture was centrifuged, washed with deionized water and ethanol, and dried to obtain a rambutan-like ZnO-N, S co-doped porous carbon composite electrode material.
[0075] First, the rambutan-like ZnO-N, S dual-doped porous carbon in the synthesized embodiment and the comparative example is used as an active material, and the binder polyvinylidene fluoride and the conductive agent conductive carbon black are mixed in a solvent and a polypyrrolidone solvent in a mass ratio of 7:2:1, and stirred to obtain a uniform slurry. The slurry is evenly coated on a copper foil, vacuum dried, and cut to obtain a negative electrode sheet. A CR2032 button battery is selected as a model, a pure lithium sheet is used as a positive electrode material, and the electrolyte is 1 mol / L LiPF 6 and a mixed solution of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1, the diaphragm is a C2400 polypropylene porous membrane, and the battery is assembled in a glove box according to the positive electrode shell, spring sheet, gasket, positive electrode lithium sheet, electrolyte, diaphragm, negative electrode sheet and negative electrode shell. Under the action of a press, a lithium-ion battery is assembled and a cycle stability test is carried out on a CHI660D electrochemical workstation with a test voltage of 0.01-3V.
[0076]
Claims
1. A rambutan-shaped ZnO-N, S dual-doped porous carbon composite electrode material, characterized in that: The rambutan-shaped ZnO-N, S dual-doped porous carbon composite electrode material and preparation method are as follows: (1) Using aluminum chloride as a catalyst, thiophene and succinyl chloride react to obtain 1,4-bis(2-thienyl)-1,4-butanedione, which then reacts with p-phenylenediamine to obtain a 2,5-dithienylpyrrole derivative containing an aromatic amino group, with the molecular formula C 18 H 14 N2S2; (2) Using 2,5-dithienylpyrrole derivatives as reactants, a polymerization reaction occurs under the action of n-butyl lithium and copper chloride as initiators to obtain polydithienylpyrrole; (3) adding polydithienyl pyrrole to a 20%-35% acetic acid solution, stirring and mixing evenly, adding terephthalaldehyde, stirring and mixing evenly, causing a cross-linking reaction, filtering, washing, and drying after the reaction is completed to obtain a super-cross-linked polydithienyl pyrrole; (4) adding the hyper-crosslinked polydithienyl pyrrole into a tube furnace and calcining it in a nitrogen atmosphere. After the calcination, cooling is performed, and the obtained sample is soaked in deionized water for 2-4 hours and then dried to obtain a N, S co-doped carbon precursor. (5) uniformly mixing the N, S co-doped carbon precursor and potassium hydroxide, transferring them to a tube furnace, and calcining them in an argon atmosphere. After the calcination, immersing, washing to neutrality, and drying, thereby obtaining N, S co-doped porous carbon; (6) Add sorbitol and zinc nitrate to deionized water and ethanol, stir well, then add sodium hydroxide and N, S co-doped porous carbon, mix well, transfer the mixed solution to a reactor, and perform an aging reaction. After the reaction is completed, centrifuge, wash, and dry to obtain a rambutan-like ZnO-N, S co-doped porous carbon composite electrode material.
2. The rambutan-shaped ZnO-N, S dual-doped porous carbon composite electrode material according to claim 1, characterized in that: In the step (3), the mass ratio of polydithienyl pyrrole to terephthalaldehyde is 100:15-25.
3. The rambutan-shaped ZnO-N, S dual-doped porous carbon composite electrode material according to claim 1, characterized in that: The temperature of the cross-linking reaction in step (3) is 50-65° C., and the time of the cross-linking reaction is 6-12 hours.
4. The rambutan-shaped ZnO-N, S dual-doped porous carbon composite electrode material according to claim 1, characterized in that: In the step (4), the heating rate of calcination is 2-5°C / min, the calcination temperature is 750-850°C, and the calcination time is 1-2h.
5. The rambutan-shaped ZnO-N, S dual-doped porous carbon composite electrode material according to claim 1, characterized in that: In the step (5), the mass ratio of the N, S co-doped carbon precursor to potassium hydroxide is 100:350-450.
6. The rambutan-shaped ZnO-N, S dual-doped porous carbon composite electrode material according to claim 1, characterized in that: In the step (5), the heating rate of calcination is 2-5°C / min, the calcination temperature is 800-850°C, and the calcination time is 2-3h.
7. The rambutan-shaped ZnO-N, S dual-doped porous carbon composite electrode material according to claim 1, characterized in that: In the step (6), the mass ratio of sorbitol, zinc nitrate, sodium hydroxide and N, S co-doped porous carbon is 40-60:52-76:110-160:
100.
8. The rambutan-shaped ZnO-N, S dual-doped porous carbon composite electrode material according to claim 1, characterized in that: The temperature of the aging reaction in step (6) is 80-100° C., and the aging reaction time is 5-10 hours.
Citation Information
Patent Citations
Lithium ion battery zinc oxide / porous carbon composite negative electrode material with high capacity and preparation method thereof
CN103606657A
Method for preparing boron-doped porous carbon spheres
CN107346821A